Nutritional Status of Patients with Long-Term Stay in the Hospital (International Journal of Food and Nutritional Sciences, 2025)
Malnutrition in hospitalized patients is a critical healthcare globally. It affects a patient’s quality of life, thereby increasing mortality and morbidity. In a hospital setting, where patients are admitted for a long term stay, infection rate increases and expenditure is also increased. The increase in malnutrition-related diseases in people with multiple comorbidities is a growing health concern, and it is strictly related to both the aging of the general population and the improvement in healthcare of note, this population group more often needs hospitalization. Between 20 and 50% of patients are present with malnutrition before hospital admission. Of note, 49% of malnourished patients that are hospitalized for more than a week maintain or face a deterioration of their previous nutritional status. Moreover, about a third of patients with a preserved nutritional status before hospital admission will develop malnutrition during hospital stay (Reziean et al, 2025). In the present study, fifty six patients were thus selected for nutritional assessment, but for anthropometry, it was possible to include only 50 patients, as 6 patients were bedridden and their weight and height measurements were not feasible. The values obtained for height and weight status in this study showed that the patients’ initial nutritional status was quite satisfactory, and compared fairly well with the ICMR (2010) values for reference man and woman and patients did not appear to be at a nutritional risk. Weight loss observed in 40% patients after 10-15 days of hospitalization was of a small magnitude and not significant (p=